The CcrM DNA Methyltransferase of Agrobacterium tumefaciens Is Essential, and Its Activity Is Cell Cycle Regulated - Kahng, Lyn Sue (American Society for Microbiology, 2001)
DNA methylation is now recognized as a regulator of multiple bacterial cellular processes. CcrM is a DNA adenine methyltransferase found in the alpha subdivision of the proteobacteria. Like the Dam enzyme, which is found primarily in Escherichia coli and other gamma proteobacteria, it does not appear to be part of a DNA restriction-modification system. The CcrM homolog of Agrobacterium tumefaciens was found to be essential for viability. Overexpression of CcrM is associated with significant abnormalities of cell morphology and DNA ploidy. Mapping of the transcriptional start site revealed a conserved binding motif for the global response regulator CtrA at the −35 position; this motif was footprinted by purified Caulobacter crescentus CtrA protein in its phosphorylated state. We have succeeded in isolating synchronized populations of Agrobacterium cells and analyzing their progression through the cell cycle. We demonstrate that DNA replication and cell division can be followed in an orderly manner and that flagellin expression is cyclic, consistent with our observation that motility varies during the cell cycle. Using these synchronized populations, we show that CcrM methylation of the chromosome is restricted to the late S phase of the cell cycle. Thus, within the alpha subdivision, there is a conserved cell cycle dependence and regulatory mechanism controlling ccrM expression.